Using the force time curve to determine centre of mass horizontal velocity at take-off during the grab start In swimming - Mourao, L.; de Jesus, Ka.; de Jesus, Ke.; Roesler, H.; Fernandes, R. J.; Vilas-Boas, J. P.; Vaz, M (Journal of Sports Science & Medicine, 2012)
The centre of mass horizontal velocity when the swimmer`s feet leave the starting block (take-off velocity) is a determinant factor for optimal start performances, and is dependent on preceding actions during the block phase. The use of a force-plate can be less-time consuming to provide concomitantly an accurate feedback on the centre of mass horizontal take-off velocity and immediate movement sequences description on starting block. This study aimed to validate concurrently the digital videography and dynamometric methods to assess the centre of mass horizontal take-off velocity. Methods: Six experienced competitive swimmers (age: 24.16 ± 3.18 years, body mass: 71.27 ± 10.61 kg, height: 1.76 ± 0.06 m), performed three maximal repetitions of the grab starting technique over a 15 m distance with 5 min rest intervals. Four above water video cameras (Sony, Sony® DCE-HC42E, Japan) and a tri-axial force plate (Bertec FP 4060-15, Bertec Corp., USA) collected synchronized 3D kinematic and dynamometric data, respectively. Twenty-four anatomical landmarks were manually digitized for each field using the APASystem (APAS, Ariel Dynamics Inc., USA) and the centre of mass horizontal take-off velocity was assessed. A MatLab routine (Mathworks Inc., USA) was written and run to process ground reaction force-time curves to calculate horizontal velocity component outcomes. The repeatability coefficient and 95% limits of agreement described by Bland and Altman (1986) were calculated. Results: The centre of mass horizontal take-off velocity values obtained between the two methods showed a repeatability coefficient of 0.43 m/s and [-0.17 to 0.68 m/s] agreement limits. A large range of limits of agreement might be explained by two major influences: (i) small bias values present in force measurement can affect integration, giving rise to relevant final velocity measurement deviations; and (ii) filters used in kinematic image processing system might increase the overall uncertainty of measurements, especially in low rate of data acquisition systems. Conclusions: Findings showed a poor agreement between kinematical and dynamometrical assessment of centre of mass horizontal take-off velocity, with large limits of agreement range. We suggested further studies with higher videometric sampling rate, and with a larger sample.